2017
DOI: 10.2174/1570161114666161025101303
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a High-Fat Diet on Cardiac iNOS in Female Rats

Abstract: Overexpression of inducible nitric oxide synthase (iNOS) is a key link between high-fat (HF) diet induced obesity and cardiovascular (CV) disease. Several studies have reported that oestradiol has cardioprotective effects that may be mediated through reduction of iNOS activity/expression. In the present study, female Wistar rats were fed a standard diet or a HF diet (balanced diet for laboratory rats enriched with 42% fat) for 10 weeks. Gene and protein expression of iNOS were measured in heart tissue. HF diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 96 publications
3
11
0
Order By: Relevance
“…we have previously demonstrated that a HF diet in the same rats used in this study caused an increase in cardiac iNOS mRNA and protein levels by a mechanism involving increased activation of Akt [60]. The mechanism by which iNOS may regulate RhoA expression in the heart appears to be a combination of transcriptional and translational upregulation of the RhoA gene and decreased degradation of the RhoA protein [56,25,61,62].…”
Section: Dzurba Et Al Reported That Pretreatment Of Ovariectomized Fsupporting
confidence: 50%
See 2 more Smart Citations
“…we have previously demonstrated that a HF diet in the same rats used in this study caused an increase in cardiac iNOS mRNA and protein levels by a mechanism involving increased activation of Akt [60]. The mechanism by which iNOS may regulate RhoA expression in the heart appears to be a combination of transcriptional and translational upregulation of the RhoA gene and decreased degradation of the RhoA protein [56,25,61,62].…”
Section: Dzurba Et Al Reported That Pretreatment Of Ovariectomized Fsupporting
confidence: 50%
“…This may be a consequence of enhanced RhoA/ROCK signalling, since it has been shown that both partial deletion of ROCK2 and its inhibition by fasudil prevents Ser 307 phosphorylation of IRS-1 in mice fed a HF diet for 17 weeks [56]. In addition, we have previously reported that in the same rats used in this study, a HF diet altered the expression of cardiac cluster of differentiation 36 (CD36) and fatty acid metabolism [60], leading to the accumulation of intramyocellular lipids, which in turn may activate serine kinases such as protein kinase C and mammalian target of rapamycin to consequently induce serine phosphorylation of IRS-1 [69,70].…”
Section: Dzurba Et Al Reported That Pretreatment Of Ovariectomized Fmentioning
confidence: 61%
See 1 more Smart Citation
“…The promoter of human gene NOS2 carries a known SNP marker (NOS2:−51T>C) of malaria resistance [86,87], which is caused by overexpression of inducible nitric oxide synthase encoded by this gene. Due to PubMed [38], we know that an NO excess is an accelerator of atherogenesis according to both physiological [88] and nutritional [89] original research articles. Therefore, the known SNP marker (NOS2:−51T>C) of malaria resistance [86,87] could be additionally regarded as a candidate SNP marker of accelerated atherogenesis (Table 3).…”
Section: Human Genes Associated With Blood Disordersmentioning
confidence: 99%
“…, 2006 ). In female rats, a high fat diet led to increased iNOS expression, and decreased levels of E2 and ERα protein ( Jovanovic et al . , 2017 ).…”
Section: Discussionmentioning
confidence: 99%